The Effect of Alkaline Treatment On the Schizostachyum Grande Fibre for Textile Applications - Nor Anuwar, Anis Amirah; Abdul Rashid, Azrin Hani; Jikan, Suzi Salwah; Roslan, Mohd Nazrul; Mohd Tahir, Abdussalam Al-Hakimi; Zolkifflee, Nurul Husna; Mohd Razal, Fathee Aizat (International Journal of Integrated Engineering, 2022)
Among commercial Malaysian bamboo species, Schizostachyum grande species are characterised by their longest internode and thinner culm wall, which allow more attainable fibres during the extraction process. However, the chemical composition of bamboo fibres is higher than any other natural fibre, resulting in coarse and stiff fibres that require alkaline treatment to develop fine fibres. This paper presents the effect of alkaline treatment concentration and soaking time on the physical properties of bamboo fibres, which were diameter and fineness. The bamboo fibre was treated with an alkaline solution at a 4 and 8 wt.% concentration for 6, 12, 18, and 24 hours. The diameter and fineness of bamboo fibre was evaluated to determine if alkaline concentration and soaking time affected the fibres. Results showed that the treated fibre diameter decreased by 19% to 67.03 ?m at 8 wt.% alkaline concentration for 12 hours of soaking time. The fibre fineness of 11.96 tex was produced at 24 hours of soaking time at 8 wt.% alkaline concentration. Alkaline treatment was effective in causing a decrease in fibre diameter and produced the finest fibre. Thinner and finer fibre was produced as alkaline concentration and soaking time increased.